The Role of Job Satisfaction in Mediating the Influence of Work Pressure and Work Overload on Turnover Intention at PT. Administrasi Medika Indonesia - Pebriasanty, Neny Dwi; Sukarno, Gendut; Anwar, Muhadjir (International Journal of Business and Applied Economics, 2024)
This research contains a quantitative methods using Lazarus' Job Stress Theory and Abraham Maslow's Hierarchy of Needs Theory, focusing on the concept of job satisfaction to manage turnover intention within the company. The purpose of this research is to determine the effect of: (1) Work Pressure on Turnover Intention, (2) Work Overload on Turnover Intention, (3) Work Pressure on Turnover Intention through Job Satisfaction, (4) Work Overload on Turnover Intention through Job Satisfaction in PT. Medical Administration. The sample for this research is employees working at PT. Medical Administration.  This research requires up to 95 respondents from outsourced employees using a simple random sampling technique. Data collection was carried out using a questionnaire instrument distributed to respondents. The analysis was carried out using the Partial Least Square (PLS) method using the SmartPLS software. Research findings indicate that: (1) Work Pressure makes a positive contribution to increasing Turnover Intention, (2) Work Overload makes a positive contribution to increasing Turnover Intention, (3) Work Pressure contributes to Turnover Intention through Job Satisfaction, (4) Work Overload contributes to Turnover Intention through Job Satisfaction. This research concludes that work pressure and work overload contribute to turnover intention through job satisfaction. The continuous workload and job stress experienced by employees must be minimized through appropriate management mechanisms to reduce burnout conditions that can lead to the intention to leave the job.